The Quebec Association of Gastroenterology Position Paper on Colorectal Cancer Screening - 2003. (1st August 2004) - Barkun, AN; Jobin, G; Cousineau, G; Dubé, S; Lahaie, R; Paré, P; Stein, B; Wassef, R
Abstract : Colorectal cancer is a leading cause of death and the third most common cancer in Canada. Evidence suggests that screening can reduce mortality rates and the cost effectiveness of a program compares favourably with initiatives for breast and cervical cancer. The objectives of the Association des gastro-entérologues du Québec Task Force were to determine the need for a policy on screening for colorectal cancer in Quebec, to evaluate the testing methods available and to propose one or more of these alternatives as part of a formal screening program, if indicated. Fecal occult blood testing (FOBT), endoscopy (including sigmoidoscopy and colonoscopy), barium enema and virtual colonoscopy were considered. Although most clinical efficacy data are available for FOBT and sigmoidoscopy, there are limitations to programs based on these strategies. FOBT has a high false positive rate and a low detection yield, and even a combination of these strategies will miss 24% of cancers. Colonoscopy is the best strategy to both detect and remove polyps and to diagnose colorectal cancer, with double contrast barium enema also being a sensitive detection method. The Task Force recommended the establishment, in Quebec, of a screening program with five- to 10-yearly double contrast barium enema or 10-yearly colonoscopy for individuals aged 50 years or older at low risk. The program should include outcome monitoring, public and professional education to increase awareness and promote compliance, and central coordination with other provincial programs. The program should be evaluated; specific billing codes for screening for colorectal cancer would help facilitate this. Formal feasibility, effectiveness and cost-effectiveness studies in Quebec are now warranted.